Chemical profiling, biological properties and environmental contaminants of stingless bee honey and propolis - Zainab, Ngaini; Hasnain, Hussain; Easter Sirah, Kelabo; Rafeah, Wahi; Saba, Farooq (Taylor & Francis Group, 2023)
Stingless bee honey is a unique edible natural product and has been used by humankind for millenniums for various purposes, mostly as food and for therapeutic uses. The compositions of honey and propolis are varied in different geographical locations which contribute to different pharmacological activities. Many studies reported on the pharmaceutical importance and properties of stingless bee honey or propolis, and the comparative study of either honey or propolis with common honey bee products. However, fewer studies reported on the significant properties of both stingless bee honey and propolis. In this review, three main aspects of stingless bee honey and propolis were discussed: the chemical profiling in terms of chemical and mineral composition, as well as their sugar components; their biological properties, and the environmental contaminants in stingless bee honey and propolis. This review is beneficial in the agriculture sector to improve the quality of honey by providing an appropriate environment for stingless bee farming.